The Implementation of EFL Online Learning - de Fretes, Delila; Lekawael, Rosina F. J. (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2022)
This study explores the effectiveness and broad adoption of online instruction for English as a Foreign Language (EFL). Considering the difficulties that instructors and students encounter in this kind of instruction, the study uses an extensive literature review approach. The goal is to underscore the positive impact of online learning on the sustainability of education and identify key factors that contribute to its effectiveness. Drawing literature from academic databases, journals, books, and reputable online platforms, the collection process is guided by specific terms like